Knowledge on intravenous therapy among undergraduate nursing students in Pokhara, Nepal: A cross-sectional study - Thapa, Cheena; Shrestha, Nisha; Banstola, Ratna Shila (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Intravenous therapy is a fundamental skill for nurses, and assessing student’s knowledge is crucial for ensuring patient safety. This study was aimed to assess the knowledge on intravenous therapy among undergraduate nursing students in Gandaki province, Pokhara.Methods: A cross-sectional study was conducted among purposively selected 208 undergraduate nursing students in Pokhara. Pretested structured self-administered questionnaire was used to collect data which was validated and reliable (r=0.85). Data was analyzed in SPSS version 22.0, using descriptive and inferential statistics (Chi-square test and logistic regression) p-value